Cover Picture: Fortschritte der Physik 2–3 / 2013. Issue 2 (1st February 2013) - Bird, J.; Kaiser, R.; Rotter, I.; Wunner, G.
<x xml:space="preserve">Abstract</x> A schematic illustration of an experimental device in which a common continuum supports a non‐local coupling between a pair of quantum point contacts. With a localized state present in one of the point contacts, the coupling to the continuum gives rise to a mesoscopic Fano resonance in this open system. For further details see the article by S. Xiao et al. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>